The Impact of In Situ Polymerization Conditions on the Structures and Properties of PANI/ZnO-Based Multiphase Composite Photocatalysts - Vanja Gilja (Catalysts, 2020)
We have synthesized polyaniline/ZnO-based (PANI/ZnO) multiphase composite photocatalysts from acid media by a newly proposed two-step in situ polymerization. The first step of synthesis yielded PANI salt required for the PANI/ZnO synergistic effect. In the second step, the aniline oxidation continued, without ZnO dissolution, and it produced PANI base. Thus, both PANI salt and base phases in the composites were detected by FTIR and UV/Vis, while the presence of both ZnO and PANI polymer was confirmed by XRD. Additionally, XRD also showed Zn5(OH)8(NO3)2·2H2O and Zn(SO4)(H2O) phases in PANI/ZnO-based multiphase composites. Furthermore, the impact of the synthesis conditions on the morphology of the composites was investigated by FE-SEM. The images displayed that ZnO particles were encapsulated in PANI sheets that were formed by the aniline oligomers. Photocatalytic evaluation of PANI/ZnO-based catalysts (i.e., degradation of Acid Blue 25 dye) was conducted and the obtained results confirmed that all the studied composites experienced the PANI/ZnO synergistic effect. It was observed that the best photocatalytic properties were held by the PANI/ZnO_2 sample due to its optimal particle size.